The Use of Iron-Enriched Yeast for the Production of Flatbread - Karolina Nowosad; Monika Sujka (Molecules, 2021)
The most common cause of iron deficiency is an improperly balanced diet, in which the body’s need for iron cannot be met by absorption of this element from food. Targeted iron supplementation and food fortification may be the main treatments for iron deficiency in the population. However, many iron-rich supplements and foods have low bioavailability of this element. In our study, we used yeast enriched with iron ions to produce flatbread. The yeast cells accumulated iron ions from the medium supplemented with Fe(NO3)3·9H2O, additionally one of the cultures was treated with pulsed electric field in order to increase the accumulation. The potential bioavailability of iron from flatbread containing 385.8 ± 4.12 mg of iron in 100 g dry mass was 10.83 ± 0.94%. All the flatbreads had a moderate glycemic index. There were no significant differences in antioxidant activity against DPPH• between flatbread with iron-enriched and non-iron-enriched yeast. Sensory evaluation showed that this product is acceptable to consumers since no metallic aftertaste was detected. Iron enriched flatbread can potentially be an alternative to dietary supplements in iron deficiency states.